The Role of the WALHI NGO in Increasing Public Knowledge and Awareness About Waste Management as a Form of Citizen Participation in Environmental Protection: A Case Study in Pondok Village, Kerinci Regency - Sihaloho, Loide; Hartanto, Rima Vien Permata; Nuryadi, Muh. Hendri (Journal of Educational Sciences, 2025)
In building a national civilization oriented toward developing civic values, strategic and systematic efforts are essential to instill knowledge and awareness of citizenship. One of these efforts is reflected in the role of the WALHI NGO in enhancing community awareness and participation in waste management as an expression of civic responsibility in the environmental sector. This study aims to analyze the role and challenges faced by WALHI Jambi in raising awareness and improving waste management in Pondok Village, Bukit Kerman District, Kerinci Regency. Using a qualitative method with a case study approach, the research explores WALHI Jambi’s initiatives through interviews, observations, and document studies analyzed using Miles and Huberman’s interactive model. The findings reveal that WALHI Jambi has played a significant role in increasing environmental awareness through public campaigns, education programs, and the formation of environmentally conscious community groups that promote ecological values and behavior change. However, several challenges persist, including low environmental literacy, strong traditional practices, limited public engagement, and internal organizational barriers. Strengthening cooperation among NGOs, government, and local communities, along with culturally rooted strategies, is crucial to fostering sustainable environmental awareness and collective action.